A MECHANISM TO PROTECT THE YOUNG GENERATION FROM MORAL THREATS - Abdurasulov Olimjon Abalboyevich (Western European Studies, 2024)
The article talks about the globalization process, stages, and the concept of moral threat, approaches and interpretations of their content. Also, the negative aspects of moral threats and their impact on national spirituality were discussed
Keywords: approach; interpretation